2001
DOI: 10.1002/1097-4636(20011205)57:3<449::aid-jbm1188>3.0.co;2-0
|View full text |Cite
|
Sign up to set email alerts
|

In vitro effects of low-intensity ultrasound stimulation on the bone cells

Abstract: Mechanical perturbations serve as extracellular signals to a variety of cells, including bone cells. Low-intensity pulsed ultrasound produces significant multifunctional effects that are directly relevant to bone formation and resorption. Ultrasound stimulation has been shown to accelerate bone-defect healing and trabecular bone regeneration. In this study, we use an in vitro bone cell culture model to investigate the effect of low-intensity pulsed ultrasound. The rat alveolar mononuclear cell-calvaria osteobl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
1
7

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 101 publications
(70 citation statements)
references
References 61 publications
2
60
1
7
Order By: Relevance
“…Our results showed that LIPUS did not significantly increase HUCPVCs cell count after a 10 minute daily applications for days 1, 7, and 14. This is in disagreement with previous studies that showed that LIPUS has a stimulatory effect on a variety of cell lines, such as osteoblasts, chondrocytes, and marrow-derived stromal cells [32][33][34][35] . This could be due to the possibility that HUCPVCs react differently to LIPUS compared to other cells.…”
Section: Discussioncontrasting
confidence: 99%
“…Our results showed that LIPUS did not significantly increase HUCPVCs cell count after a 10 minute daily applications for days 1, 7, and 14. This is in disagreement with previous studies that showed that LIPUS has a stimulatory effect on a variety of cell lines, such as osteoblasts, chondrocytes, and marrow-derived stromal cells [32][33][34][35] . This could be due to the possibility that HUCPVCs react differently to LIPUS compared to other cells.…”
Section: Discussioncontrasting
confidence: 99%
“…The primary effect of LIPUS stimulation found at the early stage of consolidation of distraction osteogenesis might be associated with enhancement of intramembranous ossification in consolidation stage as reported by others, 23 suggesting that osteoblasts might play an important role in LIPUS-induced bone formation. In fact, in vitro experiments demonstrated that LIPUS exerted mechanical stress on osteogenic cells directly to stimulate proliferation 24,25 and osteoblastic activity. 26 also stimulated osteoblasts to synthesize nitric oxide and prostaglandin E 2 (PGE 2 ) 28,29 which enhanced bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…36 The decrease of those cytokines would lead to decline in osteoclast activity. 37,38 Although LIPUS might not directly stimulate osteoclasts, it was able to stimulate osteoblast activity 25,27 which, in turn, modulated osteoclast formation. 39 This was in agreement to our radiographical and pQCT analysis results that LIPUS advanced bone mineralization processes about 2 weeks as compared with sham during an The LIPUS and sham groups were compared with statistically significant difference.…”
Section: Discussionmentioning
confidence: 99%
“…The process of facture healing includes cell proliferation and differentiation, chemotaxis, and synthesis of the extracellular matrix. LIPUS treatment elevated Runx2 mRNA expression and progressively promoted osteocalcin mRNA expression in human osteoblasts (7).…”
Section: Introductionmentioning
confidence: 90%